Advances in understanding the response of fibre-based polymer composites to shock waves and explosive blasts. (October 2019) - Mouritz, A.P.
Abstract: Fibre-based polymer composites are used in applications were there is the risk of an explosive blast. This paper presents a comprehensive review of published research into the blast performance of fibre-based composite materials, which includes fibre-reinforced polymer (FRP) laminates, fibre metal laminates, and sandwich composites with FRP facesheets. The dynamic loading experienced by composite materials under surface contact, near-field and far-field blast events is described. The various test methods used to experimentally evaluate the response of composites to shock wave and blast loading are reviewed. Experimental and modelling studies into the deformation and damage of composites caused by shock waves are also reviewed. The mechanisms by which fibre-polymer laminates, fibre metal laminates and sandwich composites absorb the shock wave energy generated by an explosive blast are analysed. The paper also reviews methods used to improve the blast performance of composites.